Markers of subclinical vascular damage in young adults with type 1 diabetes mellitus: the role of central blood pressure. Issue 12 (22nd December 2022) - Marcon, Denise; Tagetti, Angela; Piona, Claudia; Giontella, Alice; Bortolotti, Stefano; Bonafini, Sara; Carletti, Lorenza; Morandi, Anita; Trombetta, Maddalena; Maffeis, Claudio; Fava, Cristiano
Abstract : Introduction: Type 1 diabetes mellitus (T1D) is a chronic disease leading to cardiovascular complications that can be diagnosed early as subclinical vascular damage. To prevent such damage, it is important to increase knowledge of the effects of the different cardiovascular risk factors in patients with T1D. The aim of our study was to assess possible associations between markers of subclinical arterial damage and traditional cardiovascular risk factors, with a special focus on peripheral blood pressure and central blood pressure (cBP), in a sample of young adults with T1D. Patients and methods: The study included 172 T1D patients (mean age 24.7 ± 8.7 years, duration of T1D 13.5 ± 9.6 years). Pulse wave velocity (PWV), pulse wave analysis and cBP were assessed by tonometry (SphygmoCor Xcel). Carotid intima–media thickness (cIMT) and carotid distensibility coefficient (cDC) were assessed by high-resolution echo-Doppler analysis and further examined with dedicated hardware. Results: Seventeen patients (10.1%) were classified as hypertensive by office peripheral blood pressure, and 48 patients (27.9%) were classified as hypertensive by cBP. One hundred sixteen patients (68.8%) had cDC under the range of normality, one patient had a PWV (0.6%) above 10 m/s, and no patients had a cIMT above 0.9 mm. In multivariable analysis, central SBP, but not metabolic parameters, remained associated with all the markers of subclinical arterial damage [cIMT ( β = 0.288 ± 0.001; P < 0.001), PWV ( β = 0.374 ± 0.007; P < 0.001), cDC ( β = −0.149 ± 0.055; P = 0.029)]. Conclusion: The independent association between cBP and markers of subclinical vascular damage underlines the importance of haemodynamic factors in the development of early signs of macrovascular disease in T1D patients. Further studies are warranted to better define the role of cBP to stratify cardiovascular risk, to individualize the need for follow-up and to tailor preventive strategies in T1D patients.